The Role of Ocean Penetrative Solar Radiation in the Evolution of Mediterranean Storm Daniel - Karagiorgos, John; Patlakas, Platon; Vervatis, Vassilios; Sofianos, Sarantis (Remote Sensing, 2025)
Air–sea interactions play a pivotal role in shaping cyclone development and evolution. In this context, this study investigates the role of ocean optical properties and solar radiation penetration in modulating subsurface heat content and their subsequent influence on the intensity of Mediterranean cyclones. Using a regional coupled ocean–wave–atmosphere model, we conducted sensitivity experiments for Storm Daniel (2023) comparing two solar radiation penetration schemes in the ocean model component: one with a constant light attenuation depth and another with chlorophyll-dependent attenuation based on satellite estimates. Results show that the chlorophyll-driven radiative heating scheme consistently produces warmer sea surface temperatures (SSTs) prior to cyclone onset, leading to stronger cyclones characterized by deeper minimum mean sea-level pressure, intensified convective activity, and increased rainfall. However, post-storm SST cooling is also amplified due to stronger wind stress and vertical mixing, potentially influencing subsequent local atmospheric conditions. Overall, this work demonstrates that ocean bio-optical processes can meaningfully impact Mediterranean cyclone behavior, highlighting the importance of using appropriate underwater light attenuation schemes and ocean color remote sensing data in coupled models.
Keywords: Air–sea interaction; Extreme weather; Mediterranean cyclones; ocean bio-optical processes; ocean color remote sensing; ocean–wave–atmosphere coupling; penetrative solar radiation schemes; Storm Daniel